Savanna soil fertility limits growth but not survival of tropical forest tree seedlings - Viani, Ricardo A. G.; Rodrigues, Ricardo R.; Dawson, Todd E.; Oliveira, Rafael S. (Plant and soil, 2011)
Background and Aims Cerradão (Brazilian woodland savannas) and seasonally dry forests (SDF) from southeastern Brazil occur under the same climate but are remarkably distinct in species composition. The objective of this study was to evaluate the role of soil origin in the initial growth and distribution of SDF and Cerradão species. Methods We conducted a greenhouse experiment growing Cerradão and SDF tree seedlings over their soil and the soil of the contrasting vegetation type. We evaluated soil nutrient availability and seedling survivorship, growth and leaf functional traits. Results Despite the higher nutrient availability in SDF soils, soil origin did not affect seedling survivorship. The three SDF species demonstrated home-soil advantage, enhanced growth with increasing soil nutrient availability and had higher growth rates than Cerradão species, even on Cerradão soils. Growth of Cerradão seedlings was not higher on Cerradão soil and, overall, was not positively correlated with soil nutrient availability. Conclusions SDF species are fast-growing species while Cerradão trees tend to be slow-growing species. Although savanna soil reduces growth of forest species, our findings suggest that soil chemical attributes, alone, does not exclude the occurrence of SDF seedlings in Cerradão and vice-versa.